Microbial Pattern of Abnormal Vaginal Discharge in Reproductive Age Women Presenting in a Tertiary Health Facility in Imo State Nigeria - Jideuma I. Egwim; VIctor Dike; Ifeoma J. Ogugua; Hope O. Igbonagwam; Adanna V. Egwim (Nigerian Frontline Medicine Journal)
Background: Abnormal vaginal discharge, a common gynecological issue in reproductive-age women, is primarily caused by microbial pathogens. Since these organisms have been linked to cause severe consequences for the fetus and mother, it is crucial to determine their microbiome pa erns. This study, therefore assessed the microbial pattern of abnormal vaginal discharge in reproductive-age women presenting in a tertiary health facility in Imo State Nigeria